Analysis on the spatiotemporal evolutions of groundwater hydrochemistry and water quality caused by over-extraction and seawater intrusion in eastern coastal China - Chen, Weifan; Wu, Chu; Pan, Shibing; Shi, Long (Frontiers in Earth Science, 2024)
The over-extraction of groundwater has resulted in seawater intrusion and the southward migration of the saltwater interface, gradually deteriorating the groundwater quality in the Weibei Plain. In this research, groundwater samples were gathered from 46 monitoring wells for shallow groundwater during the years 2006, 2011, 2016, and 2021. The hydrochemical features of regional groundwater and the factors influencing the issue were subjected to statistical analysis. Additionally, the assessment of spatiotemporal variations in groundwater quality was conducted using the customized entropy-weighted water quality index (EWQI) method. The relationship between groundwater over-extraction and the southward intrusion of the saltwater interface was compared and analyzed. The results of this paper revealed that the Weibei Plain has been in a state of long-term over-extraction of groundwater from 2000 to 2021, with an average annual over-extraction of 118.49 million m3. The groundwater depression cone areas in the northern part of the study area increased from 3,247.37 to 4,581.34 km2 from 2006 to 2021, with the center of the cone experiencing a drop in groundwater level from −22 to −85 m. The saltwater interface shifted southward by 711.71 km2 from 2006 to 2021. In groundwater, the high concentrations of TH, TDS, and Cl− were primarily related to the seawater intrusion, while higher concentrations of NO3− were mainly determined by frequent agricultural production, industrial wastewater, and domestic sewage discharges. The groundwater hydrochemical types in the study area transitioned from predominantly HCO3·Ca-Mg type in 2006 to HCO3-Na type and SO4·Cl-Ca·Mg type in 2021 due to seawater intrusion. The results of PCA and HCA show the effects of seawater intrusion, human activities, and rock weathering on groundwater hydrochemistry. The evaluation results based on the EWQI revealed that the average value of the samples in 2021 was 101.36, which belonged to Class IV water quality standards, representing the poorest water quality among the 4 years. The southward migration of the saltwater interface led to the deterioration of groundwater quality in the groundwater depression cone areas, which gradually worsened from 2006 to 2021. The maximum increase in EWQI value was 174.68 during the period, shifting from Class III water quality to Class V water quality. Groundwater quality remained relatively better in the western and southern regions which were less affected or unaffected by seawater intrusion. The results of the study can provide a certain reference value for the sustainable management of groundwater resources and the management of groundwater pollution and seawater intrusion in the Weifang City area in the future.